Leishmania donovani resistant to Ambisome or Miltefosine exacerbates CD58 expression on NK cells and promotes trans-membrane migration in association with CD2. (August 2017) - Shivam, Pushkar; Kumari, Sarita; Jamal, Fauzia; Kumar, Vikash; Kumar, Manish; Bimal, Sanjiva; Narayan, Shyam; Das, Vidya Nand Ravi; Pandey, Krishna; Gupta, Anil Kumar; Das, Pradeep; Singh, Shubhankar Kumar
Highlights: Higher expression of CD58 but not of CD2 was observed on CD56 + cells during Visceral Leishmaniasis. Expression of CD58 on CD56 + cells were further exacerbated in Ambisome or Miltefosine relapsed VL. Ratio of CD56 + CD58 + IFN-γ + /CD56 + CD58 + IL-10 + cells reduces after stimulation with Ld. Ambisome or Miltefosine resistance Ld significantly increase CD58 expression on CD56 + cells. Antagonist to CD58 or CD2, down-regulates CD56 + cell recruitment at Ld infection site. Abstract: Visceral leishmaniasis (VL) is a disease that is associated with compromised immunity and drug un-responsiveness as well as with the emergence of drug resistance in Leishmania donovani (Ld). Ld down-modulates cellular immunity by manipulating signaling agents, including a higher expression of the adhesion molecule CD58. The expression of CD58 and CD2 on natural killer (NK) cells facilitates intercellular adhesion and signaling. The influence of drug-resistant Ld on the expression of CD58 and CD2 was addressed in this study. The mean florescence intensity (MFI) of CD58 but not of CD2 was twofold higher on CD56 + cells during VL, but was down-regulated after treatment. In addition, MFI of CD58 on CD56 + cells was further exacerbated in VL subjects who had relapsed after Ambisome or Miltefosine treatment. The same pattern of CD58 expression was also obtained upon stimulation of healthy peripheral blood mononuclear cells with Miltefosine- or Ambisome-resistant Ld. The ratio of CD56 + CD58 + IFN-γ + /CD56 + CD58 + IL-10 + cells was reduced by 6.98-fold after stimulation with Ld. Further, an antagonist to CD58 or its counter-receptor CD2 down-regulated CD56 + NK cell recruitment across a polycarbonate trans-membrane at Ld infection sites. This study reports that factors associated with drug resistance in Ld probably promote higher expression of CD58 on CD56 + cells and their migration to the infection site in association with CD2.